The Promoting Effect of Mass Media on Participatory Landscape Revitalization—An Analysis from Newspaper Coverages of Participatory Urban Gardening in China - Xiyao Zhao; Yueting Mao; Yun Qian; Qing Lin (Land, 2022)
Urban renewal urgently needs to find a new media tool to extensively promote public participation. Professionals also need strong and powerful communication tools for the public. Mass media has the ability to influence human perceptions and behaviors, but its role has been overlooked. This study aims to arouse professionals’ attention to mass media and promote interdisciplinary cooperation through empirical evidence. By observing the performance of participatory urban gardening projects in Chinese newspapers, we highlight the positive effect of mass media on participatory landscape revitalization. We selected two projects in China as samples, collected newspaper reports on them during 2017–2021, and analyzed the textual framing and report communication based on communication theory. According to the result, mass media has four positive effects that not only affect the public but also contribute to participatory landscape revitalization development. Based on the results, we discuss the consistence of views of the mass media and landscape architecture. This study suggests that landscape architecture needs to actively collaborate with public media to better leverage the role of landscape in sustainable urban transformation.